Yield and response of first and ratoon crops of eggplant (Solanum melongena) to the eggplant fruit and shoot borer (Leucinodes orbonalis) under an integrated pest management systems - Millado, Cyrose Suzie Silvosa; Rasco, Eufemio T. Jr.; Abad, Reynaldo G.; Hautea, Desiree M.; Basilio, Jerby Anne M.; Esporsado, Melvin Al Joershon R.; Te, Camille Faye S. (2012)
Eggplant (Solanum melongena) is highly valued crop with an average production of 10 t.ha-1 and contributes to nearly PhP2 billion in the Philippine economy using conventional farming methods. An integrated pest management system was designed to control the eggplant fruit and shoot borer (EFSB) for increased productivity with reduction on harmful pesticide inputs. Under a split plot in randomized complete block design, two eggplant varieties, i.e., hybrid Banate King F1 (BK) and open-pollinated Dumaguete Long Purple (DLP), were tested under four different pesticide treatments, namely, (1) control-no pesticide, (2) organic-Bird's chilli extract, (3) synthetic-spinosad + flubendiamide, and (4) combination-Bird's chilli extract + spinosad + flubendiamide. After data was obtained, the first crops were ratooned and tested under the same IPM system. Data on yield and EFSB damage of the ratoon crops were compared with the first crop as influenced by eggplant variety and pesticide treatment. All plants were grown on plots covered with polyethylene mulch sheets under a uniform fertilization and fungicide regimen.Multiple cropping with regular field sanitation and inspection were also incorporated in the IPM system. Results indicate that BK is a superior variety over DLP with a gross yield of about 40 t.ha-1 and a marketable yield of about 20 t.ha-1 in 22 harvests. Ratoon crops produced lower yield than first crops with only in 22 harvests. Ratoon crops produced lower yield than first crops with only 2 t.ha-1 in 12 harvests. Among the pesticide treatments, synthetic or combination treatments are superior over the control (no pesticide) or organic treatments. Use of open-pollinated DLP and chili spray is inferior to hybrid and synthetic or combination sprays. Chilli sprays also tends to nullify the effectiveness of synthetic pesticides when used in combination. The designed IPM system produced higher yield than conventional methods, but all treatments only provided moderate control over EFSB damage with average yield losses of about 50% in first crops and about 60% in ratoon crops.
Keywords: Eggplant; Integrated Pest Management